Soft and Hard Tissue Management in Implant Therapy—Part I: Surgical Concepts - Antonio D'Addona; Marjan Ghassemian; Luca Raffaelli; Paolo Francesco Manicone (International Journal of Biomaterials)
Implant therapy has become a reliable and predictable treatment alternative for the replacement of missing teeth with conventional removable and fixed partial dentures. Recently though, in the pursuit for improved esthetics, the literature has dedicated a considerable amount of its research on the successful maintenance and regeneration of the surrounding gingiva and bone, which are lost following extraction of a tooth. Thoroughly analyzing the anatomic situation and well-planned treatment has become a requirement, because incorrectly planned and positioned implants may jeopardize long-term esthetic and functional prognosis. In addition, many types of biocompatible materials, autogenous hard and soft tissue grafts, and different surgical techniques have been developed, and their viability has been investigated. As a result, implant specialists have gained a greater understanding of the dynamics and anatomical and biological concepts of the periodontium and peri-implant tissues both at the surgical and prosthetic phases of treatment, which contributes to better soft and hard tissue management (SHTM). This may further contribute to achieving a superior final result which is obtained by having a harmonious soft tissue profile, a correctly placed and contoured final restoration, and the reestablishment of masticatory function and phonetics.